1998
DOI: 10.1073/pnas.95.3.1184
|View full text |Cite
|
Sign up to set email alerts
|

Human erythropoietin dimers with markedly enhancedin vivo activity

Abstract: Human erythropoietin, a widely used and important therapeutic glycoprotein, has a relatively short plasma half-life due to clearance by glomerular filtration as well as by other mechanisms. We hypothesized that an erythropoietin species with a larger molecular size would exhibit an increased plasma half-life and, potentially, an enhanced biological activity. We now report the production of biologically active erythropoietin dimers and trimers by chemical crosslinking of the conventional monomeric form. We impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
39
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 21 publications
2
39
1
Order By: Relevance
“…39 DAE7 proliferation assay calibrated with human recombinant Epo determined that the Epo dimer induced a 6-fold-higher increase in hematocrit compared with the monomeric form when injected on days 1, 3, and 5 in normal mice at concentrations of 300 U/kg. A similar effect on hematocrit has been observed with chemically linked Epo dimer injected in rabbits 22 and with an Epo-Epo fusion protein injected in mice. 23 It has been postulated that this effect is mainly the result of an enhanced blood lifetime of the dimeric form.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…39 DAE7 proliferation assay calibrated with human recombinant Epo determined that the Epo dimer induced a 6-fold-higher increase in hematocrit compared with the monomeric form when injected on days 1, 3, and 5 in normal mice at concentrations of 300 U/kg. A similar effect on hematocrit has been observed with chemically linked Epo dimer injected in rabbits 22 and with an Epo-Epo fusion protein injected in mice. 23 It has been postulated that this effect is mainly the result of an enhanced blood lifetime of the dimeric form.…”
Section: Discussionsupporting
confidence: 57%
“…As with a higher Epo concentration (200 U/kg; Figure 5), no difference between monomer and dimer pharmacokinetics was observed (data not shown). Discrepancies between our data and previously published results 22,23 could be related to (1) the sequence or the length of the linker peptide, which was longer in previous studies (17 amino acid residues vs 9 residues in this study), (2) the producing Epo and Epo-Epo cell line, which may have modified the glycosylation pattern, or (3) the monomeric Epo used as reference for the pharmacokinetic studies. In this study, monomeric and dimeric Epo were produced under identical conditions, by the same cell line, without purification but by concentration of the culture medium using ultrafiltration.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Previously, we produced chemically linked Epo dimers and showed that we could achieve an increase in potency and a decreased frequency of injection, all leading to enhanced in vivo action (6). These chemically linked dimers are, in all likelihood, a mixed population of molecules, presumably consisting of more highly active isoforms and, possibly, less active ones.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that these molecules would exhibit an increased plasma half-life and would also possess enhanced activity due to facilitated binding of the repeating units to their cognate receptors and to amplification of the intracellular signaling pathways. We and others have shown previously that such molecules could be produced by chemical cross-linking (6,7). However, a fusion protein with two human erythropoietin (Epo) 1 domains linked by three to seven amino acids exhibited reduced in vitro activity compared with the wild-type monomer (8).…”
mentioning
confidence: 99%